VISUAL MARKETING TRANSFORMATION OF SOUTH JAKARTA UMKM THROUGH THE IMPLEMENTATION OF CANVA ON THE QUALITY OF PROMOTION AS A BUSINESS COMPETITOR - Fahririn, Fahririn; Siti Aminatu Zuhria; Yuherman (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
The digital era requires MSMEs to adapt visual marketing strategies in order to remain competitive. The digital era requires MSMEs to adapt visual marketing strategies in order to remain competitive. MSMEs in South Jakarta face significant challenges in optimizing social media as a promotional platform, particularly in creating engaging and professional visual content. Limited financial resources and low digital literacy are the main barriers to accessing professional graphic design services. This study aims to analyze the impact of implementing the Canva platform on improving the quality of promotions and competitiveness of SMEs in the Jagakarsa area of South Jakarta, as well as identifying the factors influencing the success of visual marketing transformation. The study uses a qualitative approach with a community service method through three stages: preparation (comprehensive survey and stakeholder coordination), implementation (face-to-face training with a modular format), and evaluation (impact monitoring through structured questionnaires and in-depth interviews). The program involved 48 SMEs focused on the culinary and handicraft sectors. The implementation of Canva demonstrated a significant improvement in the quality of SME promotional materials. There was heterogeneity in adoption levels influenced by learning motivation, resource availability, and integration with existing business processes, resulting in compelling visual outputs and cost savings compared to professional design services. SMEs that successfully integrated visual marketing into their routine operations demonstrated higher sustainability of use. The Canva platform has proven effective as a solution for democratizing graphic design for SMEs, providing affordable access to professional tools and enhancing competitiveness in the digital marketing ecosystem.